2014
DOI: 10.1038/cgt.2014.52
|View full text |Cite
|
Sign up to set email alerts
|

WAVE3 promotes epithelial–mesenchymal transition of gastric cancer through upregulation of Snail

Abstract: WAVE3, an actin cytoskeleton remodeling protein overexpressed in many kinds of cancers, has been associated with a lot of metastatic diseases. However, the role and mechanisms of the high expression of WAVE3 in human gastric cancer has not been fully elucidated. Here we demonstrated that WAVE3 was expressed in all six kinds of gastric-cancer cell lines: BGC-823, SGC-7901, AGS, MGC803, MKN28 and MKN45. Furthermore, a correlation was found between aggressiveness of these cell lines and expression of WAVE3. Next,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Immunohistochemical (IHC) data showed that WASF3 is upregulated in high-grade breast tumors (10, 14). Similar analyses show the relationship between WASF3 expression levels and poor prognosis in non-small cell lung cancer (15), gastric cancer (16), hepatocellular carcinoma (17) and prostate cancer (11,18). Thus, analysis of WASF3 expression levels in primary cancers, are consonant with the in vitro studies showing WASF3 promotes cancer cell invasion.…”
Section: Introductionmentioning
confidence: 56%
“…Immunohistochemical (IHC) data showed that WASF3 is upregulated in high-grade breast tumors (10, 14). Similar analyses show the relationship between WASF3 expression levels and poor prognosis in non-small cell lung cancer (15), gastric cancer (16), hepatocellular carcinoma (17) and prostate cancer (11,18). Thus, analysis of WASF3 expression levels in primary cancers, are consonant with the in vitro studies showing WASF3 promotes cancer cell invasion.…”
Section: Introductionmentioning
confidence: 56%
“…WAVE3 is overexpressed in certain types of cancer, including ovarian cancer ( 6 ), breast cancer ( 7 ), prostate cancer ( 8 ), hepatocellular carcinoma ( 9 ), gastric cancer ( 10 ), and colorectal cancer ( 11 ). High expression levels of WAVE3 are associated with stronger capabilities for migration and invasion in some cancer types, and researchers have discovered that WAVE3 promotes the epithelial-mesenchymal transition (EMT) process to enhance the metastatic potential of certain types of cancer ( 10 , 12 ). Moreover, WAVE3 has also been shown to be associated with cell survival in certain types of cancer ( 6 , 8 , 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…High expression levels of WAVE3 are associated with stronger capabilities for migration and invasion in some cancer types, and researchers have discovered that WAVE3 promotes the epithelial-mesenchymal transition (EMT) process to enhance the metastatic potential of certain types of cancer ( 10 , 12 ). Moreover, WAVE3 has also been shown to be associated with cell survival in certain types of cancer ( 6 , 8 , 10 12 ). The mechanisms through which WAVE3 influences the biological properties of certain types of cancer have been examined in a few studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the postulated promigratory role of other actin-related proteins and NPFs, WAVE2 has been shown to be downregulated in gastric carcinoma, and, surprisingly, WAVE2 knockdown increased gastric carcinoma cell growth, invasiveness, motility, and adhesiveness and suppressed epithelial-mesenchymal transition in vitro [ 53 ]. Conversely, it has been reported that miRNA146a-induced downregulation of WAVE2 results in impaired migration and invasion, and WAVE3 expression enhances metastasis, invasion, and proliferation activity via upregulation of Snail in gastric cancer cell lines [ 54 , 55 ]. WAVE2 is strongly expressed in colorectal carcinoma cells, but only weakly in colonic epithelium maintaining normal structure; furthermore, colocalization of Arp2 and WAVE2 is associated with tumor cell budding, an established marker for aggressive tumor behavior in colorectal carcinoma and an independent risk factor for liver metastasis in CRC [ 30 , 56 ].…”
Section: Actin-related Proteins and Nucleation-promoting Factors Imentioning
confidence: 99%